Implementasi layanan Jasa Tukang Kebun Berbasis Aplikasi - Bagus Pribadi (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2023)
In the current era, people who own land containing trees and plants have been used as buildings for business and personal interests, increasing population has resulted in increased housing needs, the use of open space for public entertainment has decreased due to the activities of people who are busy working to make ends meet. and the lack of public interest in making the environment more beautiful and sustainable. Even though the existence of a garden in a large building greatly influences the atmosphere in the environment around the building. Apart from that, one of the reasons is the lack of interest of the community in creating a beautiful environment because it is quite difficult to find the services of gardeners around where people live. The problem that occurs is that these gardeners are not exposed to all the gardens they build.